(untitled) (Eurasian Medical Research Periodical, 2023)
In the present study, from 23,296 identified publications, taking into account the inclusion and exclusion criteria, 54 publications with a total power of 47,145 patients with COVID-19 were selected and included. In all studies, data were analyzed retrospectively; the risk of developing pulmonary tuberculosis during the pandemic was higher in individuals with concomitant pathologies of the cardiovascular and endocrine systems, especially in their combination